2023
DOI: 10.1002/nau.25323
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in lower urinary tract function in mice with or without spinal cord injury

Mamoru Hashimoto,
Sergei Karnup,
Stephanie L. Daugherty
et al.

Abstract: ObjectivesWe examined sex differences of lower urinary tract function and molecular mechanisms in mice with and without spinal cord injury (SCI).MethodsSCI was induced by Th8−9 spinal cord transection in male and female mice. We evaluated cystometrograms (CMG) and electromyography (EMG) of external urethral sphincter (EUS) at 6 weeks after SCI in spinal intact (SI) and SCI mice. The mRNA levels of Piezo2 and TRPV1 were measured in L6‐S1 dorsal root ganglia (DRG). Protein levels of nerve growth factor (NGF) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…NGF stimulates the proliferation and survival of target neurons [ 50 ], and bladder NGF also lowers the threshold of TRPV1 [ 51 ]. Excessive NGF expression is involved in OAB pathogenesis by influencing bladder dysfunction through these mechanisms [ 52 ]. Some studies have found that unidentified inhibitory substances other than NO, cyclooxygenase, catecholamine, adenosine, and GABA (γ-Aminobutyric acid) are released from the urothelium upon stimulation of muscarinic receptors [ 53 , 54 ].…”
Section: Pathophysiology Of Oabmentioning
confidence: 99%
“…NGF stimulates the proliferation and survival of target neurons [ 50 ], and bladder NGF also lowers the threshold of TRPV1 [ 51 ]. Excessive NGF expression is involved in OAB pathogenesis by influencing bladder dysfunction through these mechanisms [ 52 ]. Some studies have found that unidentified inhibitory substances other than NO, cyclooxygenase, catecholamine, adenosine, and GABA (γ-Aminobutyric acid) are released from the urothelium upon stimulation of muscarinic receptors [ 53 , 54 ].…”
Section: Pathophysiology Of Oabmentioning
confidence: 99%
“…All surgical and experimental procedures in this study were performed under protocols approved by the Institutional Animal Care and Use Committee (IACUC) at the University of Maryland School of Medicine. To reduce the risk of bladder infection (32,33), we only used female mice in this study. Young adult (10-12 weeks) female CD11b KO mice were obtained from Dr. Li Zhang's lab and maintained in the UMB animal facility.…”
Section: Animals and Mouse Spinal Cord Contusion Modelmentioning
confidence: 99%
“…In males, voiding is accompanied by EUS-electromyography (EUS-EMG) busting and rhythmic 5-7 Hz EUS contractions actively pumping out portions of urine. In females, voiding occurs during a series of smooth waves of urethra relaxation, allowing passive release of urine driven by intravesical pressure (Hashimoto et al 2024) Thus, difference in mechanisms of voiding may explain the observed fact of much easier manual emptying of the BL in females than in males before reflex voiding recovers after SCI (personal observation). Restoration of reflex voiding in females also occurs earlier than in males (Saito et al 2021), which is consistent with the notion of functional dimorphism as a consequence of anatomical dimorphism.…”
Section: Figure 10mentioning
confidence: 99%